Валькирии: роман / П. Коэльо ; [перевод с португальского Д. Ружский] - Коэльо Пауло (АСТ, 2011)
Экземпляры: аб. (2018) / Инвентарный номер: 54515 / Цена: / Сис.шифр: 84(7Бра) / Авт.знак: К 76 / ББК: 84(7Бра)^VLBC/PL